Digital Transformation and Data-Driven Decision-Making in Loan Disbursement: A Case Study of BRI - Ardhi Setyarko; Erik Ridha Nugraha; Tio Anta Wibawa; Nurma Gupita Dewi (CV. Ulil Albab Corp, 2024)
Digital transformation refers to the integration of digital technologies in various aspects of an organization, leading to improved processes, customer experiences, and overall performance. Loan disbursement is a critical process in banking operations, involving the transfer of funds from a lending institution to a borrower following the approval of a loan application. The case study focuses on the successful implementation of data-driven decision- making at Bank Rakyat Indonesia (BRI). This focus on digital transformation and innovation has enabled BRI to maintain a strong market position and expand its services to a broader customer base. The digital transformation and data-driven decision-making implemented by BRI in loan disbursement have yielded significant benefits, including increased efficiency, improved accuracy, and enhanced customer experience